Factor Analysis: Nature, Mechanism and Uses in Social and Management Science Research - Nimalathasan, B. (ournal of Cost and Management Accountant, Bangladesh,, 2009)
Factor Analysis (FA) attempts to simplify complex and diverse relationships that exist among a set of observed variables by uncovering common dimensions or factors that link together the seemingly unrelated variables and consequently provides insight into the significance of underlying structure of the data. This state of affairs might produce some frustration among social and management science practitioners and even among some academicians, who find it difficult to comprehend and interpret the mechanism and results of FA. Therefore the study is designed to assist those who need to read and comprehend research articles on FA, as well as who may find it desirable to use FA in their own work.
Keywords: Factor Analysis; Nature; Mechanism; Social and Management Science